Revisiting the Growth Modulon of Corynebacterium glutamicum Under Glucose Limited Chemostat Conditions - Graf, Michaela; Haas, Thorsten; Teleki, Attila; Feith, André; Cerff, Martin; Wiechert, Wolfgang; Nöh, Katharina; Busche, Tobias; Kalinowski, Jörn; Takors, Ralf (Frontiers in Bioengineering and Biotechnology, 2020)
Increasing the growth rate of the industrial host Corynebacterium glutamicum is a promising target to rise productivities of growth coupled product formation. As a prerequisite, detailed knowledge about the tight regulation network is necessary for identifying promising metabolic engineering goals. Here, we present comprehensive metabolic and transcriptional analysis of C. glutamicum ATCC 13032 growing under glucose limited chemostat conditions with μ = 0.2, 0.3, and 0.4 h-1. Intermediates of central metabolism mostly showed rising pool sizes with increasing growth. 13C-flux analysis underlined the fundamental role of central metabolism for the supply of precursors, redox, and energy equivalents. Global, growth-associated, concerted transcriptional patterns were not detected giving rise to the conclusion that glycolysis, pentose-phosphate pathway, and citric acid cycle are predominately metabolically controlled under nutrient-limiting chemostat conditions. However, evidence is found that transcriptional regulation takes control over glycolysis once nutrient-rich growth conditions are installed.